Blow-up of nonradial solutions to attraction–repulsion chemotaxis system in two dimensions. (August 2016) - Li, Yan; Li, Yuxiang
Abstract: This paper deals with the attraction–repulsion chemotaxis system u t = Δ u − χ ∇ ⋅ ( u ∇ v ) + ξ ∇ ⋅ ( u ∇ w ), x ∈ Ω, t > 0, 0 = Δ v + α u − β v, x ∈ Ω, t > 0, 0 = Δ w + γ u − δ w, x ∈ Ω, t > 0, under homogeneous Neumann boundary conditions in a smooth bounded domain in R 2 . We study the finite-time blowup of nonradial solutions in the parameter values χ α − ξ γ > 0 and β ≠ δ .,